Pengembangan Sistem Antrian Dinas Kependudukan dan Catatan Sipil (DisDukCapil) Samarinda - Ipan Hasmadi; Zulkarnaen Zulkarnaen; Arbansyah Arbansyah (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Samarinda, as one of the major cities in East Kalimantan, faces challenges in public services, particularly in the Civil Registry and Population Office (DisDukCapil). The issue involves queues at service counters, impacting service efficiency for residents. The increasing population and the complexity of population administration contribute to the complication of the situation. We employed a prototype method to address this issue by involving developers and clients in the development process. Stages include needs analysis, design, prototype creation, evaluation, validation, and implementation. The community service's conclusion emphasizes the importance of identifying and analyzing the previous system to guide the development of a queue system that meets user needs, providing an effective solution, and enhancing service quality.